BMP Uses, Risks, and Complications in Spine Surgery - Nichols, Emma Hitt (MD Conference Express, 2015)
Bone morphogenetic proteins (BMPs) were used with increasing frequency in spine surgery after 2002, but their use has decreased as concerns have developed about possible cancer risk and complications. In this session, presenters discussed the evidence regarding BMPs and their associated cancer risk, other possible complications, and the patterns of BMP use since 2002.